Factors influence customer satisfaction at Pejabat Tenaga Kerja Seremban based on service quality dimension / Muhammad Ferdaus Zulkafli and Nurhana Aini Md Nasir - Zulkafli, Muhammad Ferdaus; Md Nasir, Nurhana Aini (Faculty of Business and Management, Universiti Teknologi MARA, 2013)
Customer satisfaction is one term that is very important for the organizations that provide services. It is because, when their customers satisfy with the service, it will help the company to achieve their goals and the level of satisfaction must maintain to help the organization maintain their reputation. If the organization can provide good services, it can build trust from their customer perception. This research study on the service quality dimensions which are reliability, empathy, assurance, tangible and responsiveness that will lead to customer’s satisfaction. The service quality dimensions are adapted from SERVQUAL MODEL that is developing by Parasuraman (1988).